Immune mechanisms in human Sarcoptes scabiei (Acari: Sarcoptidae) infestations. (27th December 2021) - Gazi, Umut; Taylan ‐ Ozkan, Aysegul; Mumcuoglu, Kosta Y.
Abstract: Scabies is a parasitic infestation of human and animal skin caused by different strains of the itch mite, Sarcoptes scabiei . The World Health Organization (WHO) has declared scabies in human as a neglected tropical disease, and today over 200 million people worldwide are affected. The two most commonly reported clinical manifestation of the condition are ordinary (OS) and crusted scabies (CS). CS, which can lead to fatal consequences due to secondary bacterial infections, is mostly observed in immunocompromised subjects but can also, although rarely, be detected in immunocompetent individuals. Innate and adaptive immune system components are involved in protection and pathogenesis of scabies, although with some differences between OS and CS. While the cutaneous immune response is dominated by CD4 + T‐cells in OS, it is mainly mediated by CD8 + T‐cells in CS. The two clinical conditions also differ in CD4 + T‐cell‐mediated immune responses with mixed TH 1/TH 2 (protective) and TH 2/TH 17 (non‐protective) immunoprofiles in OS and CS, respectively. Moreover, the development of CS is associated with early immunosuppression that is followed by deleterious immune response to uncontrolled mite proliferation. However, the immune response to scabies still needs further attention due to inconsistent results in the literature. The aim of this study is to attract more attention to this area by summarizing the current literature on innate and adaptive immune responses triggered against S . scabiei mites.